Islamic Family Law: The Legality of Interfaith Marriage the Perspective of Islamic Law and Law No. 16 of 2019 Concerning Marriage - Tahir, Palmawati; Muslih, Muhamad (KnE Social Sciences, 2024)
The introduction to this research is that the legality of interfaith marriages in Indonesia is still a polemic, so people trapped in interfaith marriages choose court institutions to legalize their marriages. The method used is the normative juridical legal research method, descriptive analytical in nature, using primary and secondary data sources. Data sources were obtained from library research. The research results show that Islamic law and marriage law prohibit interfaith marriages, so there is no need for a new formulation because the law is clear, namely, it is not valid. This research discusses how marriage between followers of different religions is seen from the perspective according to Islamic law and the marriage law, and to find out what the solution is. Keywords: marriage family law, interfaith marriage, Islamic law